2022
DOI: 10.22146/jkesvo.67626
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kelengkapan Rekam Medis Pasien Rawat Inap Fraktur Tulang Anggota Gerak di Rumah Sakit Bhayangkara Denpasar

Abstract: Latar Belakang: Rekam medis adalah berkas yang memuat atas catatan serta dokumen mengenai identitas pasien, pemeriksaan, pengobatan, tindakan, dan pelayanan lain yang telah diberikan kepada pasien. Rekam medis yang lengkap bisa menunjang mutu pelayanan suatu rumah sakit. Laporan 10 besar penyakit rawat inap RS Bhayangkara Denpasar tahun 2020 yang menempati urutan pertama adalah fraktur tulang anggota gerak. Masih banyak ketidaklengkapan rekam medis pada kasus fraktur tulang anggota gerak.Tujuan: Menganalisis k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…With the availability of supporting facilities and infrastructure, it makes it easier for officers to borrow and return without any problems or obstacles in carrying out these tasks. This research was supported by the results of Wardhina and Rahmadiliyani's 16 research explaining that the cause of the delay in returning the medical record files of inpatients at Mawar General Hospital was the completeness of filling in the medical record file itself. Files before being processed by the medical record officer must ensure that the contents are complete first.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…With the availability of supporting facilities and infrastructure, it makes it easier for officers to borrow and return without any problems or obstacles in carrying out these tasks. This research was supported by the results of Wardhina and Rahmadiliyani's 16 research explaining that the cause of the delay in returning the medical record files of inpatients at Mawar General Hospital was the completeness of filling in the medical record file itself. Files before being processed by the medical record officer must ensure that the contents are complete first.…”
Section: Discussionmentioning
confidence: 66%
“…The results of the study related to the frequency of incomplete filling of important reporting showed results that were in line with Indarti and Agustia's research 15 showing that the results of a quantitative analysis of important reporting of medical record documents at RSGM Nala Husada were 84% complete and 16% incomplete. Other supporting research, namely research by Yanti and Yulianti 16 showed that the completeness of filling in the summary form of entry and exit on the patient reporting component of cases of the Internal Medicine Polyclinic had not been completed, namely the disease diagnosis item, disease code, disease history, date of admission, condition out, the action taken and the action code where the incomplete percentage of each item is 16% incomplete and 84% complete. the highest incompleteness was found in the exit date and payment method items, namely 22% incomplete and 78% complete.…”
Section: Discussionmentioning
confidence: 99%